Agriculture in Syria : Towards the Social Market - World Bank (Washington, DC, 2013)
There are many reasons to believe that Syrian agriculture has great potential for the future. The liberalisation of agriculture in Eastern Europe delivered rapid growth in the late 1990s and early 2000s. Countries such as Armenia, Azerbaijan, Belarus, Bulgaria, Hungary, Kazachstan, Romania and Russia achieved labour productivity growth in constant US$ terms of over 7 percent between 1998 and 2004. Syria has a global comparative advantage in fruit and vegetables. It also has access to high-value markets in the Gulf Co-operation Council, Iraq and the European Union (EU). This report makes suggestions for further small and safe policy adjustments on the road to the social market. A criterion for identifying the options below is that they should not impose significant welfare losses on any target group. Changes that empower the farmer and the private trader are preferred.